PRELIMINARY IDEAS OF NECESSITY AND ACCIDENT (World Bulletin of Social Sciences, 2023)
The article describes the historical aspects of the categories of necessity and chance, the content of issues related to these categories. In the teachings of representatives of the philosophical schools of the ancient East, India and China, the specific aspects of necessity and chance, existing alternative views were analyzed